Notes on the phraseology of the Volgare in Italy between Bembo and Salviati - Sosnowski, Roman (Kwartalnik Neofilologiczny, 2026)
This article examines how phraseology, proverbs, and lexical collocations are addressed in the works of Pietro Bembo and Lionardo Salviati. While Bembo advocates for a literary model rooted in 14th-century Florentine authors, Salviati embraces both classical and popular idioms, contributing to the systematic documentation of Tuscan phraseology that would later shape the Vocabolario of the Accademia della Crusca.